The role of knowledge management processes in achieving tax excellence Applied research in the General Authority for Taxation (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The research aims to highlight the knowledge management processes in achieving tax excellence of the General Authority for Taxation as a service provider that provides many services to taxpayers and companies. The more the Authority can adopt new concepts to increase understanding and knowledge of how they are interested in the acquisition, organization and transfer of knowledge and work to provide an appropriate work environment, In attracting new taxpayers, and building long-term relationships with them, whenever reflected on performance and tax excellence. To this end, research in the analysis of its variables will depend on the questionnaire as a main tool for collecting data and information,In order to deepen the answer to the following problems, we have asked the following questions: What are the knowledge management processes and the readiness of the General Authority for Taxation? What are the dimensions of knowledge management processes (knowledge acquisition, knowledge organization, transfer of knowledge) The study is based on the importance of research on this issue by identifying the extent to which knowledge management processes affect the achievement of tax excellence, especially since tax is considered one of the main resources of the state, especially the developing countries